If only - Junger, Gil
After his impetuous musician girlfriend, Samantha (Hewitt), dies in an accident shortly after they had a fight (and nearly broke up), a grief-stricken British businessman, Ian Wyndham (Nicholls), living in London gets a chance to relieve the day all over again, in the hope of changing the events that led up to her getting killed